2018
DOI: 10.1113/jp275817
|View full text |Cite
|
Sign up to set email alerts
|

Influence of group III/IV muscle afferents on small muscle mass exercise performance: a bioenergetics perspective

Abstract: The direct influence of group III/IV muscle afferents on exercise performance remains equivocal. Therefore, all-out intermittent isometric single-leg knee-extensor exercise and phosphorous magnetic resonance spectroscopy ( P-MRS) were utilized to provide a high time resolution assessment of exercise performance and skeletal muscle bioenergetics in control conditions (CTRL) and with the attenuation of group III/IV muscle afferent feedback via lumbar intrathecal fentanyl (FENT). In both conditions, seven recreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 70 publications
6
51
1
Order By: Relevance
“…; Broxterman et al . ). Whether the reduced contractile economy with ageing is a result of inefficiencies in neural activation of the muscle, chemomechanical coupling of the myosin‐actin interaction (myofibrillar ATPase) and/or ion transport (Ca 2+ and/or Na + ‐K + ATPases) is unknown and worth further investigation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Broxterman et al . ). Whether the reduced contractile economy with ageing is a result of inefficiencies in neural activation of the muscle, chemomechanical coupling of the myosin‐actin interaction (myofibrillar ATPase) and/or ion transport (Ca 2+ and/or Na + ‐K + ATPases) is unknown and worth further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…However, surprisingly, we did not observe a greater age-related depletion in the [ATP] during the exercise suggesting that the old adults may have relied to a greater extent on the adenylate kinase reaction to maintain a stable [ATP]. Although the explanation remains unclear, the disproportionate increase in [P i ] relative to the decrease in [PCr] was also observed when the ATP cost of contraction was increased in young men by attenuating group III//IV afferent feedback via lumbar intrathecal fentanyl administration (Broxterman et al 2017;Broxterman et al 2018). Whether the reduced contractile economy with ageing is a result of inefficiencies in neural activation of the muscle, chemomechanical coupling of the myosin-actin interaction (myofibrillar ATPase) and/or ion transport (Ca 2+ and/or Na + -K + ATPases) is unknown and worth further investigation.…”
Section: Age-related Increases In Fatigability Are Explained By An Inmentioning
confidence: 99%
“…Moreover, both muscle activation, as estimated by electromyographic activity, and time under tension have been shown to be directly related to the perceived exertion response [19,22]. It appears that metabolite accumulation can affect afferent feedback in the central nervous system and thus decrease performance and contractile efficiency [24]. Moreover, this may in turn influence RPE.…”
Section: Introductionmentioning
confidence: 99%
“…within the severe‐intensity domain) (Dekerle et al., ; Ferguson et al., ). Several lines of evidence indicate that CP/CT is aerobic in nature (Broxterman et al., ) and seems to represent a ‘critical threshold’ above which task failure is coincident with complete utilization of W,trueV̇normalO2 max attainment and similar muscle fatigue (i.e. decreased maximal voluntary force) (Burnley, Vanhatalo, & Jones, ; Jones, Wilkerson, DiMenna, Fulford, & Poole, ; Jones et al., ; Poole, Ward, Gardner, & Whipp, ).…”
Section: Introductionmentioning
confidence: 99%
“…reduced maximal voluntary contraction) and peripheral fatigue and the magnitude of W ′ during handgrip exercise performed with blood flow occlusion. More recently, studies have demonstrated that group III/IV muscle afferents constrain the intramuscular perturbations and muscle contraction efficiency during small muscle mass exercises performed using both submaximal (Broxtermann et al., ) and maximal (Broxterman et al., ) muscle contractions.…”
Section: Introductionmentioning
confidence: 99%